Analysis of the Effectiveness using Overall Equipment Effectiveness in Identifying Six Big Losses on SY-GF 250H Lathe (Case Study CV Jasa Bhakti) - Naufal Muhammad Rafi Fauzan; Fahriza Nurul Azizah (Jurnal Rekayasa Sistem & Industri, 2022)
CV Jasa Bhakti is a manufacturing industry company that produces agricultural machinery and automotivespare parts. During the production process, the SY-GF 2500H lathe has problems, namely engine damagewhich causes the production machine to not operate and causes downtime which can cause losses andaffect the effectiveness of the SY-GF 2500H lathe. The Overall Equipment Effectiveness (OEE) method isused to measure the level of effectiveness on a machine by using three main components, namelyavailability rate, performance rate, and quality rate to identify types of losses based on six big losses, theaverage OEE result of 75% is still below the standard world class with factors that affect the low OEE,namely the performance rate of 79%, while the losses that affect the effectiveness value of the performancerate are idle and minor stoppage of 6% and reduce speed losses of 35%. By analyzing the root causes ofthe problem through a fishbone diagram, and five whys analysis. From this method, it can be concludedthat the causes of the low effectiveness value on the performance rate which are influenced by idle andminor stoppage and reduced speed losses are human factors, machines, materials, and methods.